PROMISE: um modelo de confiabilidade para sistemas de economia colaborativa - Geanderson Esteves dos Santos (2018)
Sharing economy is a new kind of economy that is reaching an increasing number of people around the world. This concept is based on four main characteristics: (1) significant supply of spare resources from some individuals, (2) a large amount of people wanting to share those resources, (3) trust among people who do not know each other, and (4) the recognition by participants of the benefits of sharing. Many different types of resources can be shared in this economy, for example, temporary housing, transportation, storage, and a variety of other goods and services. Despite the large success of this type of platform, many concerns have arisen in communities that utilize these services, in particular following incidents involving sexual abuse, theft, verbal assault, and other social problems. To avoid these problems, these platforms have implemented solutions that allow users to develop more trust in other participants. In general, these mechanisms of generating trust involve the construction of a reputation based on user satisfaction (Bilgihan et al., 2015), both with respect to those offering the service (providers) and those receiving the service (consumers). This work proposes a detailed study on the development of trust in sharing economy. In the first step, a Systematic Literature Review (SLR) was applied to the main computer digital library databases. The SLR revealed a series of trust indicators that could be grouped into a trust framework. In addition, its application allowed the identification of the types of values exchanged in different sharing economy systems, as well as the state of the art in the research on trust in these systems. For triangulation of the framework and a more in-depth study of its real impact, qualitative methods were applied using as case study two of the largest representatives of this new type of economy: Airbnb and Couchsurfing. These systems were selected as the focus of the analysis because they have similar purposes, i.e., renting properties, however, have completely different exchange values, i.e., Airbnb is monetary and Couchsurfing is social. These systems were analyzed systematically through the reconstruction of the metamessage from the designers to users. The purpose of this analysis was to verify which strategies have been used by designers to create a reliable environment for users based on the trust indicators. Later, a study of feedback collected from Trustpilot on the opinions of users with both systems, aimed to find out what impact the indicators had on users’ experiences with systems. The results of the qualitative analyses showed that the trust framework indicators allowed a detailed description of aspects relevant to shared economy systems, as well as guiding the discussion about the differences between the two systems analyzed in this research. Finally, this work proposes an in-depth study of several aspects of trust that make users feel more comfortable using services provided by sharing economy systems.